Legal Protection of Notaries in Executing Their Office in the Digital Era - Nur Kusumah, Rizqa; Hanim, Lathifah (Sultan Agung Notary Law Review, 2025)
This study aims to analyze the forms of legal protection for Notaries in carrying out their duties in the digital era and identify obstacles that arise in its implementation. The digitalization of legal services has encouraged the use of electronic documents and electronic signatures, but at the same time raises new issues related to the validity of deeds, official authority, data security, and the risk of criminalization for Notaries as public officials. This study uses a normative-empirical legal research method with a statutory, conceptual, and sociological approach. Primary data was obtained through interviews with active Notaries, while secondary data was obtained from a library study of laws and related literature. Data were analyzed qualitatively with a deductive mindset to obtain a comprehensive picture of the dynamics of legal protection in the digital era. The research results show that legal protection for Notaries in the digital era includes preventive protection through the regulation of authority, supervision by the Supervisory Board and the Notary Honorary Council, and electronic data security mechanisms in accordance with the ITE Law and the PDP Law. Repressive protection is realized through dispute resolution and legal mechanisms in the event of alleged misconduct. However, several obstacles were found, including a lack of norms regarding electronic deeds, limited technological infrastructure, low digital literacy among Notaries, and the absence of uniform data security standards. This research recommends the establishment of specific regulations regarding digital notaries, strengthening cybersecurity systems, and improving digital competence for Notaries to create a safe and equitable digital notary system.